The Sociocultural Psychology as a Postformal Theory of Academic Achievement: Interrogating Formal Education - Chetan Sinha (International Journal of Educational Psychology, 2013)
The present paper interrogates the dominance of formal education. As formal education system relies on ability based academic achievement as a goal, exploring post-formal approaches, such as sociocultural notion of academic achievement is the hallmark of present paper. An attempt is made to interrogate the existing cultural dominance in formal education referring to the need of ability stereotyped groups, not discarding formal education totally. Taking the route from sociocultural experience of children, paper also explores their process of social identification with the present educational system. The way students identification gets constructed and co-constructed, either acknowledges or discards the achievement domain of education, is the major point of contention. Overall, the paper tries to answer the basic psychological question that “Why particular form of education and achievement under the mainstream discourse of education is legitimized and valued in the social psychological representations?”